PERUBAHAN BENTUK DAN MAKNA PATUNG TAU-TAU TORAJA - Simatupang, Devi Oktavia (2017)
Tau-Tau sculptures are one of the unique and rich aspects of this island's artwork. But there is still little written which can clearly describe the form and meaning of these sculptures.The questions raised in this thesis were: How has the form of the Tau-Tau in Toraja changed over time, how has the meaning that was contained in this form evolved and, additionally, what factors have contributed to the movements within the form of the Tau-Tau. Based on these questions, this study aims to, in the first part, know and describe the changing form of the Tau Tau in Toraja. Next, to describe the evolution of the significance of the sculpture and finally, the evolution of the meaning contained within the Tau Tau. Thiis study utilized a descriptive method, supported through anthropological and semiotic methodology. The semiotic analysis technique used was interpretive. Data that was used in the study was observational, collected from interviews in addition to documented studies.Thee results are as follows; 1) The form of the Tau Tau changed over time from abstract to more realistic forms; 2) The meaning of the Tau Tau has changed from being "a house to the soul" to representing a memory of appreciation for the deceased; 3) This transition occurred due to several factors: the contact with the outside world. the change of belief and the entry of technology and science. For further research it would be necessary to conduct a direct reconstruction of the damaged Tau Tau on site as well as museum pieces. These results can be a source of material for art teachers on various levels, especially serving as materials with respect to learning Cultural arts in Toraja. However the connection between specific local cultural evolution and a students understanding of the value of local cultural creativity can be relevant regardless of location.---- Patung Tau-Tau merupakan salah satu bentuk keunikan dan kekayaan nusantara dalam bentuk karya seni. namun masih sedikit dokumentasi tertulis yang mendeskripsikan secara jelas terkait bentuk dan makna dari patung Tau-Tau. Rumusan masalah yang diangkat dalam penelitian ini yaitu : 1) bagaimana perkembangan bentuk patung Tau-Tau Toraja?; 2) Bagaimana pergeseran makna yang terkandung dalam patung Tau-Tau Toraja? 3) Apa saja faktor perubahan bentuk dan makna patung Tau-Tau Toraja? Berdasarkan rumusan masalah tersebut maka tujuan penelitian ini untuk: 1) Mengetahui dan mendeskripsikan perkembangan bentuk patung Tau-Tau Toraja; 2) Mengetahui dan mendeskripsikan pergeseran makna yang terkandung dalam patung Tau-Tau Toraja;3) Mengetahui dan mendeskripsikan faktor perubahan bentuk dan makna patung Tau-Tau Toraja. Metode yang digunakan dalam penelitian ini adalah metode deskriptif, dengan model pendekatan antropologi dan semiotika. Teknik analisis semiotik dalam penelitian ini adalah dengan metode semiotika interpretatif. Data yang digunakan untuk penelitian ini adalah data hasil obserbasi, wawancara, dan studi dokumentasi. Hasil penelitian ini adalah; 1) Bentuk Tau-Tau bergeser dari bentuk figuratif menjadi bentuk realis; 2) Patung Tau-Tau awalnya dimaknai sebagai wadah jiwa nenek moyang kini bergeser sebagai kenangan atau penghargaan kepada almarhum; 3) Perubahan bentuk dan makna patung Tau-Tau terjadi karena beberapa faktor, yaitu persentuhan dengan dunia luar, pergeseran kepercayaan, masuknya teknologi, serta masuknya ilmu pengetahuan. Untuk penelitian selanjutnya perlu melakukan rekonstruksi langsung pada Tau-Tau yang rusak di situs maupun museum. Hasil penelitian ini dapat menjadi sumber bahan ajar bagi para guru seni budaya di berbagai tingkat satuan pendidikan, khususnya sebagai bahan ajar pada pembelajaran Seni Budaya di sekolah-sekolah lokal daerah Toraja dengan kedalaman materi yang disesuaikan.